Levilactobacillus brevis, autochthonous to cucumber fermentation, is unable to utilize citric acid and encodes for a putative 1,2-propanediol utilization microcompartment - Pérez-Díaz, Ilenys M.; Page, Clinton A.; Mendez-Sandoval, Lesley; Johanningsmeier, Suzanne D. (Frontiers in Microbiology, 2023)
The metabolic versatility of Levilactobacillus brevis, a heterofermentative lactic acid bacterium, could benefit environmentally compatible and low salt cucumber fermentation. The biodiversity of Lvb. brevis autochthonous to cucumber fermentation was studied using genotypic and phenotypic analyses to identify unique adjunct cultures. A group of 131 isolates autochthonous to industrial fermentations was screened using rep-PCR-(GTG)5 and a fermentation ability assay under varied combinations of salt (0 or 6%), initial pH (4.0 or 5.2), and temperature (15 or 30°C). No apparent similarities were observed among the seven and nine clusters in the genotypic and phenotypic dendrograms, respectively. A total of 14 isolates representing the observed biodiversity were subjected to comparative genome analysis. The autochthonous Lvb. brevis clustered apart from allochthonous isolates, as their genomes lack templates for citrate lyase, several putative hypothetical proteins, and some plasmid- and phage-associated proteins. Four and two representative autochthonous and allochthonous Lvb. brevis, respectively, were subjected to phenotype microarray analysis using an Omnilog. Growth of all Lvb. brevis strains was supported to various levels by glucose, fructose, gentiobiose, 1,2-propanediol, and propionic acid, whereas the allochthonous isolate ATCC14890 was unique in utilizing citric acid. All the Lvb. brevis genomes encode for 1,2-propanediol utilization microcompartments. This study identified a unique Lvb. brevis strain, autochthonous to cucumber, as a potential functional adjunct culture for commercial fermentation that is distinct in metabolic activities from allochthonous isolates of the same species.